Acute responses of muscle oxygen saturation during different cluster training configurations in resistance-trained individuals - Guardado, I.; Guerra, A.; Pino, B.; Camacho, G.; Andrada, R. (Biology of Sport, 2021)
This study compared the perceptual responses, physiological indicators and technical parameters between different training protocols focused on upper body exercises. A randomized crossover design was performed, and 12 trained individuals (age: 27.1 ± 5.7 years; height: 173.7 ± 10.7 cm; BMI: 23.9 ± 2.3) completed three resistance training sessions under different protocols separated by at least 72 h: traditional training (TT) (4 x 6 repetitions at 85% of 1RM with 120 s of rest between sets), cluster 1 (CL1) (4 x 2+2+2 repetitions at 85% of 1RM with 15 s of intra-rep rest and 80 s between sets), and cluster 2 (CL2) (24 repetitions at 85% of 1RM with 15 s of inter-set recovery). Before training, arterial blood pressure (BP) and repetitions to failure of pull-up and push-up (FT) were collected. Muscle oxygen saturation (SmO2) in the chest and movement velocity were evaluated in barbell bench press during the training session. After finishing, lactate, BP, rate of perceived exertion and FT were assessed. The percentage of velocity loss (TT: 19.24%; CL1: 5.02% and CL2: 7.30%) in the bench press and lactate concentration (TT: 8.90 mmol·l-1; CL1: 6.13 mmol·l-1 and CL2: 5.48 mmol·l-1) were significantly higher (p < 0.05) for TT compared to both CLs. RPE values were higher (p < 0.05) in TT compared to CL1 (7.95 a.u. vs. 6.91 a.u., respectively). No differences (p > 0.05) were found between protocols for SmO2, BP, FT, pain or heart rate between set configurations. Cluster configurations allow one to maintain higher movement velocity and lower lactate and RPE values compared to a traditional configuration, but with similar concentrations of SmO2.